Acquired Resistance to Antituberculosis Drugs in England, Wales, and Northern Ireland, 2000–2015 - Loutet, Miranda G. (Emerg Infect Dis, 2018)
Among tuberculosis (TB) patients, acquired resistance to anti-TB drugs represents a failure in the treatment pathway. To improve diagnosis and care for patients with drug-resistant TB, we examined the epidemiology and risk factors associated with acquired drug resistance during 2000–2015 among TB patients in England, Wales, and Northern Ireland. We found acquired resistance in 0.2% (158/67,710) of patients with culture-confirmed TB. Using multivariate logistic regression, we identified the following factors associated with acquired drug resistance: having pulmonary disease; initial resistance to isoniazid, rifampin, or both; a previous TB episode; and being born in China or South Africa. Treatment outcomes were worse for patients with than without acquired resistance. Although acquired resistance is rare in the study area, certain patient groups are at higher risk. Identifying these patients and ensuring that adequate resources are available for treatment may prevent acquisition of resistance, thereby limiting transmission of drug-resistant strains of mycobacteria.